Determinants Of Intention To Use E-Commerce Based On The Technology Acceptance Model - Anggraeni, Windi Ariesti (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Due to the development of e-commerce platforms in Indonesia, it is important to understand the factors that encourage user acceptance. This study explores the determinants of users' behavioral intention to use e-commerce platforms based on the Technology Acceptance Model (TAM). TAM is represented by perceived ease of use and perceived usefulness. This research is a quantitative study with data collection techniques through distributing questionnaires. The sample in this study was 100 respondents. The analysis technique used multiple linear regression analysis through SPSS 26. The results showed that perceived ease of use and perceived usefulness had a significant positive effect on behavioral intention to use. This provides actionable insights for businesses to conduct sales strategies by considering consumer perceptions of e-commerce users.